Pengaruh Kepercayaan, Kecintaan dan Keterikatan Emosional pada Loyalitas Merek - Arthur Sitaniapessy; Zany Irayati Aunalal; Harry A. P. Sitaniapessy (Univiversitas Dr. Djar Wattiheluw, 2025)
This study aims to examine the effect of brand trust, brand love, and brand emotional attachment on brand loyalty. Respondents in this study are customers who own and use OPPO brand Smartphones in Ambon City. This research uses multiple regression analyses and validity and reliability tests to test research instruments. The results showed that the three hypotheses proposed were accepted, which means that brand trust, brand love, and emotional brand attachment affect brand loyalty.